Four young teenage girls playing ping pong outdoors - Unknown:::Creator::::::::::::
Negative shows four young teenage girls playing ping pong on a picnic bench that has been modified into a ping pong table. They are outside and are probably at the YWCA"S Camp Ayun Mapu in Big Basin, California.